Fate and transport of insensitive high explosives in the environment - Temple, Tracey (Cranfield University, 2018)
The research undertaken for this thesis has contributed to better understanding of the fate and transport on insensitive high explosives (IHE) formulations and suitable extraction methods from soil. Investigations into the dissolution behavior of hexahydro-1,3,5-triazine (RDX) from Polymer Bonded Explosives (PXB) showed that the polymer retained almost 97% of the explosive filling. This indicates that these formulations release their contents slowly although consistently suggesting that cumulative contamination may occur in the environment. Due to low release of RDX from the polymer it was necessary to validate the findings by ensuring all explosives were accounted for. As there was no existing extraction methods for PXB a novel Accelerated Solvent Extraction (ASE) method was successfully developed and optimized. To further understand IHE behaviours in the environment, fate and transport of IHE in soil was then considered. However, as RDX behaviour is well understood attention was then turned to IMX formulations in soil. Again suitable extraction for IHE in soil had not been reported, therefore a comparison of suitable extraction methods for IHE constituents in soil was undertaken. Results showed extraction of IHE is dependent on soil types, which highlighted the need to pre-determine extraction efficiency for soil type and targeted contamination. Therefore pre-testing extraction with known concentrations is recommended. This research was then applied to understanding the behaviour of the mixed constituents in soil, following column transportation studies. Results contributed to and supported work from the literature on the behaviour of individual IHE constituents suggesting that these explosives in combination did not adversely interact with each other when in soil. The novelty of this work was the investigation of IHE as mixtures rather than individually. This work has provided valuable insights into the behaviour of two different IHE (PBX and IMX) in the environment, and has communicated suitable extraction procedures to enable full quantification of contaminant concentrations.